Local Aronson-Bénilan Estimates for Porous Medium Equations Under Ricci Flow (Journal of Partial Differential Equations, 2020)
In this work we derive local gradient estimates of the Aronson-Bénilan type for positive solutions of porous medium equations under Ricci flow with bounded Ricci curvature. As an application, we derive a Harnack type inequality.